The applications of ultrasonic sensor - Mat Yassim, Salehah; Rahiman, Mohd. Hafiz Fazalul; Abdul Rahim, Ruzairi; Wahid, Herman; Mohammad Din, Shahrulnizahani (Penerbit UTHM, 2017)
Ultrasonic sensor usually used for distance measurement and obstacles detection. This sensor is low cost and suitable for range up to few metres for distance measurement applications. However, this sensor has limitations which are wide beam width and sensitivity to the mirror – like surfaces. Despite the disadvantages, there are several applications of these sensors such as wireless obstacle detection, collision control and avoidance, distance measurement and smart parking system. Each of the applications has difference approaches suggested by the researchers. Baharuddin M et al. proposed that in order to give a reliable distance measurement, both infrared and ultrasonic sensors are used together [1]. This paper discussed about four applications of ultrasonic sensors in details which are wireless obstacle detection, collision control and avoidance, distance measurement and smart parking system.